2017
DOI: 10.3892/mmr.2017.8354
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin 1-7 ameliorates caerulein-induced inflammation in pancreatic acinar cells by downregulating Toll-like receptor 4/nuclear factor-κB expression

Abstract: The present study aimed to investigate the effects of angiotensin (Ang) 1–7 on caerulein (CAE)-stimulated nuclear factor (NF)-κB, Toll-like receptor (TLR4) and cytokine expression using pancreatic acinar AR42J cells. AR42J cells were treated with 10 nmol/l CAE for various durations. In addition, cells were pretreated with various concentrations of Ang 1–7 or A779, a specific antagonist of Ang 1–7, and were stimulated with CAE for 12 h. Control cells were treated with vehicle (F-12K complete medium with 2% feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Caerulein-treated AR42J cells were used in a model of AP in vitro as previously described (25)(26)(27). In the current study, AR42J cells were incubated with 10 nM caerulein for 0, 2, 4, 6 or 8 h. The results demonstrated that caerulein triggered the inflammatory response and apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…Caerulein-treated AR42J cells were used in a model of AP in vitro as previously described (25)(26)(27). In the current study, AR42J cells were incubated with 10 nM caerulein for 0, 2, 4, 6 or 8 h. The results demonstrated that caerulein triggered the inflammatory response and apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…In 2012, our team rst found that high levels of Ang1-7 were expressed in the pancreas of a mouse SAP model, and that the basal level of Ang1-7 in the pancreatic tissue and serum of the SAP mice was between 3 and 15 µg/mL [23] . We also found that Ang1-7 could exert a protective role in restoring pancreatic microcirculation as well as reducing pancreatic injury and in ammatory responses [24][25][26] . However, the other effects of Ang1-7 on the pancreatic response in AP remain unclear.…”
Section: Introductionmentioning
confidence: 55%
“…In vitro studies, an increase in IL-10 production was observed in the supernatant of pancreatic acinar cells after stimulation with TNF- α [ 19 ]. A previous study also found, in CER-stimulated AR42J pancreatic acinar cells, that the expression of IL-10 was markedly increased in gene level [ 40 ]. However, another research demonstrated that, in the supernatant of pancreatic acinar cells treated with lipopo1ysaccharide, the levels of IL-10 in culture supernatant decreased with the lipopo1ysaccharide concentration.…”
Section: Discussionmentioning
confidence: 80%